Indirect dynamics in a highly exoergic substitution reaction - Mikosch, Jochen; Zhang, Jiaxu; Trippel, Sebastian; Eichhorn, Christoph; Otto, Rico; Sun, Rui; de Jong, Wibe A.; Weidemüller, Matthias; Hase, William L.; Wester, Roland (Journal of the American Chemical Society, 2013)
The highly exoergic nucleophilic substitution reaction F- + CH3I shows reaction dynamics strikingly different from that of substitution reactions of larger halogen anions. Over a wide range of collision energies, a large fraction of indirect scattering via a long-lived hydrogen-bonded complex is found both in crossed-beam imaging experiments and in direct chemical dynamics simulations. Our measured differential scattering cross sections show large-angle scattering and low product velocities for all collision energies, resulting from efficient transfer of the collision energy to internal energy of the CH3F reaction product. Both findings are in strong contrast to the previously studied substitution reaction of Cl- + CH3I [ Science2008, 319, 183-186] at all but the lowest collision energies, a discrepancy that was not captured in a subsequent study at only a low collision energy [ J. Phys. Chem. Lett.2010, 1, 2747-2752]. Our direct chemical dynamics simulations at the DFT/B97-1 level of theory show that the reaction is dominated by three atomic-level mechanisms, an indirect reaction proceeding via an F--HCH2I hydrogen-bonded complex, a direct rebound, and a direct stripping reaction. The indirect mechanism is found to contribute about one-half of the overall substitution reaction rate at both low and high collision energies. This large fraction of indirect scattering at high collision energy is particularly surprising, because the barrier for the F--HCH2I complex to form products is only 0.10 eV. Overall, experiment and simulation agree very favorably in both the scattering angle and the product internal energy distributions.